(untitled) (TEST Ticontre. Theory Text Translation, 2023)
This paper focuses on some elements of Fenoglio’s texts, from the Appunti partigiani to the lates, often unfinished, written in 1962-1963. Many constants (i.e., many “nuclei of sense” which are proposed with high frequency) are shown, as well as many changes of perspective. In this sense Fenoglio’s partial or whole alter egos take on the author’s biographic traits, while at the same time presente other, this time fictional, traits, on the basis of the desired narrative inventio. On this topic some general opinions are proposed, which stem from textual examples mostly taken from the last novels, from the fantastic short stories (as Il letterato Franz Laszlo Melas), and dramatic texts (as Lo sbandato, also known as Solitudine). In questo contributo vengono messe a fuoco alcune caratteristiche dei testi fenogliani a partire già dagli Appunti partigiani e sino a quelli, spesso incompiuti, del 1962-63. Emergono varie costanti (ossia ‘nuclei di senso’ che tornano con alta frequenza), ma anche la tendenza a variazioni profonde della prospettiva adottata. Così, gli alter ego parziali o totali di Fenoglio assorbono di sicuro tratti biografici e storici, e tuttavia ne esibiscono pure altri molto diversi e finzionali, a seconda dell’inventio narrativa perseguita. Su questo aspetto vengono proposte considerazioni generali, però sempre a partire da alcuni esempi concreti, tratti in particolare dagli ultimi romanzi ma pure dai racconti fantastici (come Il letterato Franz Laszlo Melas) e da testi teatrali (come Lo sbandato, di solito indicato come Solitudine).